Finite-Time Stability Analysis for Delayed Fuzzy Hadamard Fractional-Order Systems - Hamdi Gassara; Mehdi Tlija; Lassaad Mchiri; Abdellatif Ben Makhlouf (Fractal and Fractional)
This paper focuses on the Finite-Time Stability Analysis (FTSA) problem for a Hadamard fractional-order system with time delay represented by a Delayed Takagi–Sugeno Fuzzy Model (DTSFM). Based on the Linear Matrix Inequality (LMI) approach, we propose two methods for FTSA. The first procedure is accomplished in two steps, while the second one is provided in only one step. The proposed results are extended to the case of DTSFM with uncertainties. An example is proposed to validate these results and to demonstrate the advantages of the one-step results compared to the two-step procedure.